Nanobodies: COVID-19 and Future Perspectives - Valenzuela-Nieto, Guillermo; Miranda-Chacon, Zaray; Salinas-Rebolledo, Constanza; Jara, Ronald; Cuevas, Alexei; Berking, Anne; Rojas-Fernandez, Alejandro (Frontiers in Drug Discovery, 2022)
The COVID-19 pandemic has driven biotechnological developments to provide new and more effective tools for prophylaxis, diagnosis, and therapy. Historically, monoclonal antibodies have been valuable tools; however, the pandemic has shown some weaknesses, such as production limitations at a global scale. An alternative to conventional monoclonal antibodies are nanobodies, recombinant fragments of the variable region of single-domain antibodies derived mainly from the Camelidae family. Nanobodies have multiple characteristic benefits: they are small (15 KDa) and have remarkable refolding capability and unlimited possibilities for modifications due to their recombinant nature. Here, we review the application of nanobodies in diagnosis and treatment of SARS-CoV-2 infection.